PENYULUHAN PERENCANAAN MANAJEMEN DANA DESA - Malikhatun, Irna; Putra, Purnama; Tirtajaya, Mas Deden (DEVOSI, 2021)
Village funds are funds sourced from the APBN which are intended for villages that are transferred through the district/city regional budget. These funds are used to finance the administration of government, implementation of development, community development and empowerment of rural communities. However, there are some governments who do not understand the distribution of village funds properly so that counseling is needed on village fund management. The method used in this activity is counseling. One of the objectives of counseling is to provide an understanding of village fund planning.